Comparison of Vicia villosa establishment under different cultivation seasons and methods in the Homand Absard Research Station - A. Mohebby (Desert, 2020)
Homand Absard Rangeland Research Station is located 70 km northeast of tehran and 15 km southeast of Damavand with an altitude of 1972 m a.s.l., an average annual rainfall of 333 mm,  and a cold semi-steppe climate. In order to compare  the seed production of Vicia villosa under different cultivation seasons and methods, the seeds were initially collected from natural habitats similar to the mentioned station. Afterwards, seed characteristics  such as viability, and seed vigorwere examined. Two sowing methods, namely row seeding and seeding with rainfall storage, through crescent contour trenches and spring and autumn sowing dates, were considered in a complete randomized block design with three replications. Statistical analysis was performed by independent t-test using SPSS 21 software.  According to the obtained results, no establishment was recorded for spring sowing; furthermore, in autumn sowing,  the two cultivation methods were not significantly different in terms of establishment (p <0.05). However, the results of mean comparisons showed that in autumn sowing, the crescent seeding with an average seed production of 68.36% was superior to the row seeding with an average seed production of 59.12%.